Assessment of the transaction costs on post-harvest maize value chain peformance in Tanzania: A survey of selected maize smallholder farmers in Kongwa District Council - Dodoma region - Rutatola, Prisca Pascrates (Mzumbe University, 2024)
A Dissertation Submitted in Partial/Fulfillment of the Requirements for Award of the Degree of Master of Science in Procurement and Supply Chain Management (MSc. PSCM) of Mzumbe University. 2019